2016
DOI: 10.1073/pnas.1609287113
|View full text |Cite
|
Sign up to set email alerts
|

Roles for small noncoding RNAs in silencing of retrotransposons in the mammalian brain

Abstract: Piwi-interacting RNAs (piRNAs), long thought to be restricted to germline, have recently been discovered in neurons of Aplysia, with a role in the epigenetic regulation of gene expression underlying long-term memory. We here ask whether piwi/piRNAs are also expressed and have functional roles in the mammalian brain. Large-scale RNA sequencing and subsequent analysis of protein expression revealed the presence in brain of several piRNA biogenesis factors including a mouse piwi (Mili), as well as small RNAs, alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 54 publications
2
74
0
Order By: Relevance
“…However, PIWI/piRNAs are reportedly expressed in the nervous system of flies, Aplysia, and mice (Lee et al, 2011; Nandi et al, 2016; Perrat et al, 2013; Rajasethupathy et al, 2012). In Aplysia sensory neurons neuronal piRNAs function in long-term facilitation (Rajasethupathy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, PIWI/piRNAs are reportedly expressed in the nervous system of flies, Aplysia, and mice (Lee et al, 2011; Nandi et al, 2016; Perrat et al, 2013; Rajasethupathy et al, 2012). In Aplysia sensory neurons neuronal piRNAs function in long-term facilitation (Rajasethupathy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent exploration of neuronal piRNAs identified approximately 30,000 piRNAs from mouse brain tissue (Ghosheh, Seridi, Ryu, Takahashi, Orlando, Carninci, and Ravasi, 2016) and suggested that these brain-derived piRNAs are most similar to those associated with PIWIL2 in mouse testes. Another study identified low-level expression of truncated PIWIL2 in the adult mouse brain, with hypomethylation of transposons and behavioural defects observed in Piwil2 knockout mice (Nandi, Chandramohan, Fioriti, Melnick, Hébert, Mason, Rajasethupathy, and Kandel, 2016). We have also previously demonstrated that the Piwi-like genes Piwil1 and Piwil2 are expressed in cultured mouse neurons, and have shown that they are dynamically regulated by neuronal activation, and are involved in transcriptional regulation of activityinduced gene expression (Leighton, Zhao, Li, Dai, Marshall, Liu, Wang, Zajaczkowski, Khandelwal, and Kumar, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…These reports are congruent with the finding that de novo coding mutations in human Piwil genes are strongly associated with autism-spectrum disorders (Iossifov et al, 2014) which are increasingly understood to involve aberrant organisation of cortical neurons (Nunes, Peatfield, Vakorin, and Doesburg, 2018;Packer, 2016). In addition, Nandi et al found that Piwil2 knockout mice are hyperactive and that males show reduced anxiety (Nandi et al, 2016); because the genetic absence of Piwil2 is present from conception, it is likely that this phenotype is also developmental. In the present study, we have demonstrated for the first time that targeted manipulation of the Piwi pathway in the adult mammalian brain affects behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…is a master regulator of piRNA mediated DNA methylation and an inhibitor of retrotransposition (47,48). PIWIL2 also regulates the expression of plasticityrelated genes in the adult brain, and disruption of the piwi pathway in HC enhances contextual fear memory in mice (49).…”
Section: Maternal Immune Activation Induces Brain Transcriptomic Chanmentioning
confidence: 99%